Sweet's Syndrome Associated with Pediatric Acute Myeloid Leukemia: A Case Report and Concise Review of Literature - Anirudh Venkatesh; Vasudeva Bhat; Archana Melavarige Venkatagiri; Vishwapriya Godkhindi; Vinay Munikoty (Indian Journal of Medical and Paediatric Oncology)
Sweet's syndrome (SS) is an inflammatory skin condition characterized by sudden onset of fever, painful skin lesions, and neutrophilic infiltration of affected tissues. The systemic association of SS include infections, drugs, malignancy, and autoimmune disorders. We describe a case of a 6-year-old pediatric male patient who was previously treated with conventional chemotherapy for acute myeloid leukemia (AML). He presented with prolonged fever and diffuse erythematous papules over the face, neck, trunk, arms, and legs. Further evaluation revealed relapse of AML following which he was initiated on salvage chemotherapy. Initial impression of the skin lesions was cutaneous infiltration of myeloid malignancy and hence not separately addressed treatment wise apart from chemotherapy. However, as the lesions persisted following first cycle of chemotherapy, a skin biopsy was pursued that revealed SS. The lesions responded only after initiation of systemic steroids and colchicine alongside chemotherapy. Early identification and histological confirmation aided treatment of above condition. The clinical rarity, diagnostic clues, and a brief review of published literature has been described. The case reports emphasizes the importance of histopathological evaluation of cutaneous lesions in hematologic malignancy and systematic approach to treatment. The case report emphasizes the need for strong clinical suspicion, importance of histopathological evaluation, and systematic approach to treatment.